Amputation Versus Staged Reconstruction for Severe Fibular Hemimelia: Assessment of Psychosocial and Quality-of-Life Status and Physical Functioning in Childhood. Issue 2 (April 2019) - Birch, John G.; Paley, Dror; Herzenberg, John E.; Morton, Anne; Ward, Shana; Riddle, Russ; Specht, Stacy; Cummings, Don; Tulchin-Francis, Kirsten
Abstract : Background: Fibular hemimelia, a congenital disorder characterized by the partial or complete absence of the fibula, tibial growth inhibition, and foot and ankle deformity and deficiency, is the most common deficiency of long bones. The purpose of the present study of children with congenital fibular hemimelia was to examine the functional and psychosocial outcomes at a minimum of 2 years after treatment either with amputation and a prosthesis or with reconstruction and lengthening. Methods: Twenty children who were managed with primary amputation were compared with 22 children who were managed with staged limb reconstruction. The average age of the patients at the time of evaluation was 9 years (range, 5 to 15 years). Patients and parents completed psychosocial, quality-of-life, and satisfaction surveys. Patients underwent instrumented gait analysis and a timed 25 or 50-yard dash. The number and nature of surgical procedures were recorded from a retrospective chart review. Results: Families of children managed with amputation had lower economic and educational levels and were more ethnically diverse compared with the families of children managed with limb reconstruction. Scores on psychosocial and quality-of-life surveys were comparable with those from healthy patient populations. Parents of males treated with amputation perceived a lower school-related quality of life for their child; socioeconomic and ethnic differences between groups might account for this finding. Statistically but not clinically significant differences were measured during instrumented gait analysis at a self-selected walking speed and during a timed 25 or 50-yard dash. The majority of patients and parents reported satisfaction with the treatment method selected and would select the same treatment method again. Conclusions: At this interim stage of growth, there were no significant functional or psychological differences between groups. Both groups were satisfied with the outcome in mid-childhood, irrespective of the selection of amputation or limb reconstruction. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.